2019
DOI: 10.4103/sajc.sajc_264_17
|View full text |Cite
|
Sign up to set email alerts
|

Burden of acute toxicities in head-and-neck radiation therapy: A single-institutional experience

Abstract: Introduction: Combined modality therapy is the standard of care in locally advanced head-and-neck cancer (HNC). The incidence of acute toxicities increases with additional therapy. The present study investigated the incidence and patterns of mucositis, dysphagia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…Esse resultado pode sugerir que, após a terceira semana de radioterapia, o paciente fica mais suscetível à queda no estado nutricional em decorrência do agravo dos sintomas, o que pode também ser consequência da toxicidade causada pelo tratamento. Assemelhando-se a esses resultados, um estudo retrospectivo realizado na Índia com pacientes de cabeça e pescoço em tratamento radioterápico mostrou que os indivíduos desenvolveram mucosite e disfagia a partir da terceira semana do tratamento 30 . Pan et al 31 avaliaram o estado nutricional de pacientes com câncer de esôfago em quimiorradioterapia e encontraram prevalência de 83% de desnutrição, sugerindo, com esses resultados, a implementação da intervenção nutricional no setor de radioterapia 31 .…”
Section: Discussionunclassified
“…Esse resultado pode sugerir que, após a terceira semana de radioterapia, o paciente fica mais suscetível à queda no estado nutricional em decorrência do agravo dos sintomas, o que pode também ser consequência da toxicidade causada pelo tratamento. Assemelhando-se a esses resultados, um estudo retrospectivo realizado na Índia com pacientes de cabeça e pescoço em tratamento radioterápico mostrou que os indivíduos desenvolveram mucosite e disfagia a partir da terceira semana do tratamento 30 . Pan et al 31 avaliaram o estado nutricional de pacientes com câncer de esôfago em quimiorradioterapia e encontraram prevalência de 83% de desnutrição, sugerindo, com esses resultados, a implementação da intervenção nutricional no setor de radioterapia 31 .…”
Section: Discussionunclassified
“…The University of Washington Quality of Life (UW-QOL) questionnaire swallowing subscale [42,63,65,71], the M.D. Anderson Dysphagia Inventory (MDADI) [41,62,68,125], and the Common Terminology Criteria for Adverse Event [74,[77][78][79][80][81] were the most commonly used instruments to assess dysphagia. Jager-Wittenaar et al reported that approximately 28% of patients (oral, pharynx, and larynx) experienced dysphagia at diagnosis, likely as a result of the disease itself [60].…”
Section: Eating and Nutritional Status Dysphagiamentioning
confidence: 99%
“…The prevalence of decreased appetite was reported among 10 studies [5,30,38,40,41,45,58,69,73,81]. Bond et al reported that, overall, 96% of their patients reported trouble with appetite [30].…”
Section: Changes In Appetitementioning
confidence: 99%
See 2 more Smart Citations